Analysis of the land use structure of the waterfront areas of the river Odra in Wrocław based on local plans - Adamiczka, Hanna (Analiza struktury przeznaczenia terenów przybrzeżnych rzeki Odry we Wrocławiu na podstawie planów miejscowych, 2021)
The river Odra (Oder) in Wrocław is essential for the city as it constitutes a significant part of the urban fabric. The possibilities of its use depend on the degree of its development planning, and its length allows for functional differentiation. The article aims to present the spatial policy of Wrocław concerning the waterfront areas of the Odra. The degree of coverage of these areas by local spatial development plans was analysed. The methods used include desk research, case study, analysis of the researched areas using up-to-date cartographic materials, literature analysis, and the legal status. Theonclusions may constitute an introduction to in-depth research on the spatial solutions of individual functions.
Biblioteka Regionalisty, 2021, Nr 21, s. 1-14
Keywords: Odra river; land use; city; Wrocław; Odra (rzeka); przeznaczenie terenów; miasto